The Mediation Effect on the Relationship Between Political Connections and Firm Value: Empirical Evidence from the Financial Industry in Indonesia - Khristina Yunita; Mustaruddin Saleh; Wendy (Universitas Hayam Wuruk Perbanas, 2025)
This investigation explores CSR's potential mediating function in the political connection-firm value relationship. The analysis utilizes 437 annual reports from Indonesia Stock Exchange-listed financial sector corporations spanning 2014-2021. Data analysis reveals that CSR successfully mediates the political connection-firm value relationship. Additional findings demonstrate that political connections exert positive and significant effects on firm value, while CSR spending patterns differ significantly between politically connected and non-connected organizations. Robustness testing employing identical variables with alternative indicators maintains result consistency.